Huajuapan Lithostratigraphic Map, Puebla and Oaxaca states, Mexico (E14-D14) - Claudia Cristina Mendoza-Rosales; Gilberto Silva-Romo; Yoalli Bianii Hernández-Marmolejo; Emiliano Campos-Madrigal (Journal of Maps)
This paper presents a 1:50,000 scale map and lithostratigraphic synthesis of the Huajuapan region, which has one of Mexico's most complete geological records. The region represents a critical area for understanding the marine flooding process after the breakup of Pangea. This process formed small extensional basins, such as the Ayuquila basin, and dismantled a primary fluvial system that drained the ancient central Pacific slope of Pangea. In the Huajuapan region, the Ayuquila basin developed in a tectonic SSE–NNW extension framework that prevailed from the Middle Jurassic to the Turonian. In its beginnings, this basin developed a thick siliciclastic fluvial deposit during the Middle Jurassic. Later, during the Late Jurassic, although with local unconformities, the deposition of marine successions began. Marine deposits continued throughout the Cretaceous. During the Cenozoic, continental conditions were re-established with clastic-evaporite successions and volcanic activity.